Daily Behavior of Red Tilapia (Oreochromis niloticus) Cultivated in Diferent Aeration and Filtration - Nurizka Ayu Setiani; Kasiyati Kasiyati; Sunarno Sunarno; Muhammad Anwar Djaelani (Bioma : Jurnal Ilmiah Biologi, 2023)
Decreased water quality in red tilapia (Oreochromis niloticus) aquaculture indicates that low dissolved oxygen availability will affect fish behavior. One of the efforts to improve water quality is through the addition of aerators and filters. Aerators and filters increase the supply of dissolved oxygen and minimize feed waste in the aquaculture pond water. This study aims to analyze of different aeration and filtration or a combination of the daily behavior patterns of tilapia including eating behavior, aggressive behavior. The study was conducted for 1 month.This study used 24 red tilapia with a length of about 8-12 cm. The research design used in this study was a completely randomized design (CRD) with 4 treatment groups and 6 replications. The treatments were ANF group (use of single aerator without filter), AANF group (use of dual aerator without filter), AF group (use of single aerator with filter), and group AAF (use of dual aerator with filter). The data collected includes the daily behavior of red tilapia and water quality. Analysis of the daily eating, aggressive and comfortable behavior of red tilapia was carried out by observing video recordings and recording behavior recording techniques at intervals of 1-2 minutes based on duration and frequency. The results showed that the use of different aerators and filters or their combination had a significantly different effect (P<0,05) on the daily behavior of red tilapia. The conclusion of this study was the raising used of multiple aerators and filters can improve the quality of aquaculture water so that it has a positive impact on feeding, foraging, and schooling behavior in the growth phase of tilapia. Key words: quality water, aerator, filterd, aily behavior